Treatment of avulsion fractures of the pelvis in adolescent athletes: A scoping literature review - Di Maria, Fabrizio; Testa, Gianluca; Sammartino, Fabio; Sorrentino, Marco; Petrantoni, Vincenzo; Pavone, Vito (Frontiers in Pediatrics, 2022)
Avulsion fractures of the pelvis and hip region are typical injuries in adolescent athletes. Avulsion sites include the muscle tendon origin or insertion, and treating these injuries surgically or conservatively remains a debated issue. The main goals of this review were to assess and summarize injury types and sites, treatment-related clinical outcomes, and return to sport for adolescent patients with a pelvis avulsion fracture and to provide support for making treatment decisions. The PubMed database was searched in November 2021 to identify all published articles from 2000 to 2021 that reported the outcome and return to sport after conservative or surgical treatment. Eighteen studies with 453 patients were included in this review. The age range was 13.6 to 16.8 years. The most common injury site the was anterior superior iliac spine (37%), followed by the anterior inferior iliac spine (31%), ischial tuberosity (14%), lesser trochanter (9%), iliac crest (8%), and superior corner of the pubic symphysis (1%). Overall complications were lower in the surgical group compared to the conservative group. The rate of return to pre-injury activity level was greater in patients who underwent surgical treatment (p<0.05). In conclusion, surgery is preferred for major dislocation and fragment size, providing a better return-to-sport rate and decreasing the risk of complications.